The Technical Efficiency of the Coffee Processing Industry in the Province of West Java - Sari, Wilda Widya; Asngari, Imam; Apriani, Deassy (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of coffee in West Java has experienced a very rapid increase in production. Coffee is a commodity that has economic value and is a superior commodity that helps the economy and GDP in West Java. Therefore, this research has the purpose of determine the effect factors of production on the output and measuring technical efficiency in the coffee processing industry in West Java. The type of data used is secondary data related to the coffee processing industry for the period 2011 to 2020. The research method used is the Stochastic Frontier Analysis approach using the Cobb-Douglas production function. The results of the study indicate that the coffee processing industry in West Java during the period from 2011 to 2020 is not technically efficient with a coefficient of 0.76. The variable of capital has a significant negative effect on the output produced by producers in the coffee processing industry, while the variable of labor and raw materials has a significant positive impact on the output produced by producers in the coffee processing industry in West Java.